Rancang Bangun Aplikasi Pemesanan Makanan Online Pada Restoran Cepat Saji Berbasis Mobile Application (Studi Kasus Chicken Mania Cabang Rungkut) - Qadhafi, Muammar; Sukmaaji, Anjik; Purnama, Rangsang (Jurnal JSIKA, 2012)
Food ordering using the telephone is a common way adopted by most of the restaurant to handle the delivery order. Based on the results of a survey conducted by the author on 9-15 September 2011 with 20 respondents, found the fact that in ordering food by phone, customers often face constraints include a time-consuming ordering process, the cost of a phone conversation increasingly along the length of time on the phone, and difficulty responding to the other person´s intentions because of signal interruption of communication service providers or manner of speech that are less understood. One solution to solve these constraints is make the online food ordering application based on mobile application that is aimed for customer at chicken mania fast-food restaurant. Through these applications, customers can easily view a list of the latest food menu offered by the restaurants and make online food ordering. Keyword: Ordering Food, Restaurant, Mobile Application, J2ME.